Effect of preemptive intravenous ketorolac and bupivacaine infiltration on post operative pethidine consumption - a comparative study - Ahmed, Jalal Uddin; Islam, Md Shahidul; Islam, Md Shafiqul; Mandal, Mantosh Kumar; Islam, Mohammad Sirajul; Shamsuzzoha, Md; Akhtaruzzaman, AKM (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Preemptive analgesia significantly reduces postoperative analgesic requirement. Multi modal approach for preemption has greater range of benefit and its use in treating postoperative pain has gaining popularity. Objectives: To observe the effect of preemptive bupivacaine infiltration and intravenous ketorolac on postoperative pethidine consumption in single and multiple preemptive techniques. Methods: One hundred and twenty patients of ASA physical status I&II requiring lower abdominal surgery under general anaesthesia were randomly allocated in four groups. Gr- A received bupivacaine infiltration and ketorolac injection, Gr-B received intravenous Ketorolac injection, Gr-C bupivacaine infiltration and Gr- D received nothing regarded as Control group. Data were analyzed by students t test, ANOVA and chi-square test as appropriate. Results: Patients characteristics, duration of surgery, haemodynamic status were comparable in four groups. Pain intensity in VAS was significantly reduced in Gr-A (p<0.00) than other three groups. Total pethidine consumption was also reduced significantly in Gr-A (p<0.05). Conclusion: Preemptive analgesics using in multiple modes gives better postoperative analgesia and patient comfort and less postoperative complications. DOI: http://dx.doi.org/10.3329/jbsa.v23i1.18155 Journal of BSA, 2010; 23(1): 25-29